Numerical investigation of off-design conditions for an axial-turbo-expander in a transcritical organic Rankine cycle (TRC) system. (September 2017) - Li, Yi-Chen; Hsieh, Jui-Ching; Chang, Yun-Yuan; Lee, Yuh-Ren
Abstract: The performance of a transcritical organic Rankine cycle (TRC) system is affected by the heat source conditions of the exhaust gases resulting from a turbo-expander under off-design conditions. In the present study, the axial-turbo-expander of the TRC system under the design point was designed through 1-D aerodynamic theory and validated using a computational fluid dynamics (CFD) solver. The CFD solver was also used to simulate and analyze the thermal-fluid field of the turbine under various heat source conditions to determine the turbine efficiency under off-design point. The axial-turbo-expander in the TRC system, with R134a serving as the working fluid, was numerically examined to investigate the turbine performance at expander inlet temperatures of 140–115 °C and circulated loop mass flow rates of 15–12.5 kg/s. The results revealed that the isentropic efficiency of the turbine sharply dropped as the circulated loop mass flow rate increased at mw > 14.5 kg/s. However, the isentropic efficiency was only slightly affected by Tin_exp at Tin_exp > 130°C. In conclusion, the temperature of the circulated loop was increased to fix the mass flow rate of the circulated loop at the increasing thermal power of the exhaust gases due to the isentropic of the turbine slightly affected by the increasing temperature of the heat source. In contrast to the increasing thermal power of the exhaust gases, the mass flow rate of the circulated loop was decreased at the decreasing thermal power of the heat source.